Nickel‐mediated Ortho C(sp2)−H Alkoxylation of Amides. Issue 46 (9th December 2022) - Xu, Peng; Tang, Ying‐Ying; Chen, Yi‐Tian; Bai, Ji‐Rong; Zhou, Pin; Wang, Ling‐ling; Sun, Xiao‐Nan; Zhou, Quan‐Fa
Abstract: In this paper, we described nickel‐mediated C(sp 2 )−H alkoxylation of amide directed by the bidentate auxiliary directing group. The method was proved efficiently to achieve alkoxide derivatives by available alcohol as substrate. We verified the protocol exhibited good yields, which showed great functional group compatibility and broad‐range substrate. Abstract : A novel method with Ni(II)‐mediated C(sp 2 )−H alkoxylation of amide which using tethered oxazoline as directing group to give alkoxy compounds from available alcohol in 30–87 % yield. The method exhibited good yields and high‐functional group compatibility, which provide an alternative protocol for flexibly accessing substituted alkoxy compounds.